Estudio de prefactibilidad de la micro – central hidroeléctrica de Tununtunumba Chazuta - Chung Rojas, Carlos Enrique (1998)
The present > research work called: "FEASIBILITY STUDY OF THE MICRO hydroelectric power PLANT WATHERFALLS - ~.fiAZUTA0, pr-etende point Jos most important technical aspects that need to be cuen1a in this type of project, because its further construction will contribute to the development of the agro-industrial and commercial activities, contributing in this way to ·mejorar the level of life of the inhabitants of the Chazuta district in particular and of the San Martín region in general. Them peoples of the interior of our region, between Jos that is can locate to the District of Chazuta and them eight centers villages in study, cross by an of them worst crisis, being the agriculture an of its main sources of life whose products that cultivated not have a value added, not cuen1an with minimum systems of health or roads by where can market their products a system of electrification, the cultural level of its inhabitants even worse...